MAIN TENDENCIES IN SPATIAL ARRANGEMENT AND FURNISHING OF THE CLASSROOM IN THE 1st THIRD OF THE 20th CENTURY - Косенко, Д. Ю (Art and Design, 2019)
Purpose of the article is to discover features of the arrangement and furnishing of the school learning space in the 1st third of the 20th century. Methodology is based on the historical and evolutionary princsple. Source base includes scientific, technical and popular literature of the period, material artefacts. Results. At the turn of 20th century strong movement for renewing of pedagogy rises; the movement based on child-centered principle is known as “reform-pedagogy” in Europe and “progressive education” in the USA. Progressive educators came to conclude that new pedagogical approaches also demand changes in the classroom equipment. Furnishing and spatial arrangement of the classroom are treated not only from the point of working convenience, but as essential part of pedagogical concept and, even more, as social and cultural phenomena. New types of classroom furniture are developed and improved, namely desks with horizontal or variable-sloped worksurface and freestanding students’ chairs, not attached to desks. Innovations in spatial arrangement are based on two approaches: functional zoning on the subject or thematic basis and flexible arrangement of pupils’ workplaces. Mentioned tendencies at that time are improved in alternative or experimental schools. Attempts to rearrange the spaces of public schools basing on mentioned approaches started in the USSR in the late 1920th, but were stopped in early 1930th, when experiments in the Soviet educational system were banned. Scientific novelty. Main tendencies in classroom spatial arrangement and furnishing in the 1st third of the 20th century are analized and summarized in the context of the progressive education movement. The furnishing of Soviet (including Ukrainian) schools of the period is discussed; similarities and differences in the development of classroom space in USSR, Western Europe and USA are revealed. Practical significance. Review of the development of the school learning space in 1st third of the 20th century contributes to the holistic picture of educational design as a historical and cultural phenomenon. Understanding the patterns of historical development of the educational space is of practical importance for the conceptualization and prediction of trends in modern educational design.